Prosody Analysis of Mariah Carey’s 1999 Billboard Award Speech and Its Contribution to EFL - Setiawan, Heri (Journal of ELT Research, 2017)
Prosodic elements are the essential elements in human beings’ speech that can be used to know what the speakers of an utterance exactly mean when they are speaking. This research was a work of analysis on prosody of speech to know the emotion and the meaning of utterances. Descriptive qualitative type of research model was employed in this research. The object of the research was Mariah Carey’s speech when she was receiving a special award named the Billboard artist of the decade in 1999. The researcher was interested in not only knowing about Mariah Carey’s emotion and meaning when she was delivering her speech but also finding other uses of prosodic elements which were not found in the supporting previous literatures used in this research. Moreover, the possible contribution which these research findings could contribute to the EFL teaching and learning was also addressed. It is evident that prosody definitely has significant contribution in EFL teaching and learning especially in improving speaking and reading comprehension skills.